2012
DOI: 10.1093/annonc/mds057
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of everolimus in patients with locally advanced or metastatic transitional cell carcinoma of the urothelial tract: clinical activity, molecular response, and biomarkers

Abstract: Everolimus showed clinical activity in advanced TCC. The profile of the plasma angiogenesis-related proteins suggested a role of the everolimus antiangiogenic properties in disease control. PTEN loss might be associated with everolimus resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 43 publications
6
89
1
2
Order By: Relevance
“…Là encore, les données cliniques pour proposer une intervention thérapeutique sur ces aberrations spécifiques sont limitées. Par exemple, l'efficacité des inhibiteurs de mTOR en cas de perte de la protéine (phosphatase) PTEN est très discutée (16,17). Les gains ou les pertes des gènes ne se traduisent d'ailleurs pas systématiquement par des surexpressions ou des absences des protéines correspondantes.…”
Section: Conditions Pre-analytiques Et Resultats D'analyseunclassified
See 1 more Smart Citation
“…Là encore, les données cliniques pour proposer une intervention thérapeutique sur ces aberrations spécifiques sont limitées. Par exemple, l'efficacité des inhibiteurs de mTOR en cas de perte de la protéine (phosphatase) PTEN est très discutée (16,17). Les gains ou les pertes des gènes ne se traduisent d'ailleurs pas systématiquement par des surexpressions ou des absences des protéines correspondantes.…”
Section: Conditions Pre-analytiques Et Resultats D'analyseunclassified
“…De façon simpliste, l'amplification et/ou la mutation activatrice d'un gène dit « pilote fort » est à privilégier comme cible. A l'opposé, l'activation supposée d'une voie (par exemple PI3K/AKT/mTOR) offre des opportunités de traitement (inhibiteurs de PI3K, d'AKT ou de mTOR), mais n'est que rarement prédictive de l'efficacité de ces traitements (16)(17)(18). Dans les deux cas, hors indication approuvée formellement, les patients doivent être traités dans le cadre de protocoles de recherche clinique formalisés.…”
Section: Importance Des Rcp Moleculairesunclassified
“…Indeed, preclinical studies using bladder cancer cell models or xenografted mice demonstrated that inhibition of mTOR by everolimus inhibited bladder cancer cell growth in vitro and in xenografted mice [19]. Subsequently, clinical trials evaluating the mTOR inhibitors everolimus or temsirolimus in this population of patients have been performed but failed to meet their primary objectives despite some prolonged responses [26,27,29]. The results of our multicenter single-arm phase II trial showed for the first time a clinical benefit of temsirolimus for the treatment of patients with relapsed bladder cancer after first-line chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of toxicity, both trials showed a similar safety profile with equivalent rates (20%) of grade 3-4 adverse events (mainly hematologic toxicity and fatigue), indicating an acceptable tolerance in patients with an ECOG status ≤2 and a rate of visceral metastases of approximately 80%, which is highly representative of such kind of population. The first phase II trial with everolimus reported a clinical activity with a 2-month non progression rate of 27% in a cohort of 28 assessable patients [26]. The second study was performed in a larger cohort of 45 patients and reported a 2-month non-progression rate of 51%, which is almost identical to the results of our study, despite the enrollment of a significant proportion of patients who received 2 or more additional lines of treatment following first line platinum-based chemotherapy [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation